PENETRALISIR CO PADA RUANGAN SMOKING AREA MENGGUNAKAN CORONA DISCHARGE - Handoko, Agung Budi; S., Yudha Rohman; P., Tri Satya (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This study aims to propose a neutralize device for CO caused by cigarette smoke using plasma corona discharge, where it can ionize dirty air becoming clean air. The device requires DC-DC, blower, sensor PIR, and minimum system micro controller. PIR censor is used to detect incoming person into smoking room, data from censor are analyzed using micro controller to activate blower and converter DC-DC. After blower sucked cigarette smoke in the room, it will be flowed via pipe into reactor corona discharge, so the air full of CO is ionized making it clean. If the PIR censor n longer detect any movement, then within one minute the blower and reactor corona discharge will automatically stop operating.Using two converters DC-DC possessing voltage of 18KV and 22.2KV, CO gas can be reduced well, as showed by the laboratory test where the smoke cigarette with CO gas of 3ppm prior to activation of plasma corona discharge becomes 0ppm after the activation.